Driving Path Predication Based Routing Protocol in Vehicular Ad hoc Networks. (21st February 2013) - Feng, Yong; Wang, Feng; Liao, Jingjing; Qian, Qian
Abstract : The vehicular mobility is reflection and extension of the human social activity. Since human trajectories show a high degree of temporal and spatial regularity, thus vehicular driving paths are predictable to a large extent. In this paper, we firstly analyze the predictabilities of different types of vehicles and then propose a new driving path predication based routing protocol (DPPR). With hello messages to broadcast vehicles' driving path predication information to neighbor vehicles, DPPR can observably increase the successful ratio to find the proper next hop vehicles that move toward the optimal expected road in intersection areas. In roads with sparse vehicle density, DPPR utilizes vehicles to carry messages to roads with high vehicle density while the messages' forward paths partially coincide with the vehicles' driving paths. Moreover, as to messages that can tolerate long delay, they can be carried to destinations by vehicles whose driving paths will pass the messages' destination in order to optimize bandwidth utilization. Simulation results demonstrate the effectiveness of the proposed DPPR protocol.